PENGARUH BIAYA OVERHEAD PABRIK TERHADAP EFISIENSI BIAYA PRODUKSI - Retno Santi Nur Azizah; Aqilah Az Zahra; Dian Hakip Nurdiansyah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research is focused on the Effect of Factory Overhead Costs on Production Cost Efficiency on PT. Charoen Pokphand Indonesia Tbk Year 2016-2020. This research aims to find out and reanalyze: 1) Factory Overhead Costs by PT Charoen Pokphand Indonesia Tbk;2) Production Costs incurred by PT Charoen Pokphand Indonesia Tbk;3) Effect of Factory Overhead Costs on production cost efficiency at PT Charoen Pokphand Indonesia Tbk. The research methods used in this research are associative methods with quantitative approaches. The data source in this study is primary data. As for analyzing the data obtained, simple regrecation analysis, correlation coefficient analysis, determination coefficient analysis, and data processing showed that factory overhead costs negatively affect production cost efficiency at PT Charoen Pokphand Indonesia Tbk. This means that at PT Charoen Pokphand Indonesia Tbk, cost control has not been implemented optimally, because this is evidenced by the inefficiency in production costs so that the realization of production costs is greater than the production cost budget. Keywords: Factory Overhead Costs and Production Cost Efficiency.